Novel Synthesis of Pyrido[2,3-b]quinoxaline-3-carboxylate Derivatives via One-Pot Buchwald Amination–Cyclization - Hajri, Majdi; Khoumeri, Omar; Abderrahim, Raoudha; Terme, Thierry; Vanelle, Patrice (Synthesis, 2023)
A novel series of pyrido[2,3-b]quinoxaline-3-carboxylate derivatives was synthesized in short reaction times and in moderate to good yields by using a palladium catalyst in a one-pot Buchwald amination/cyclization reaction.
Keywords: quinoxalines; nucleophilic substitutions; malonic esters; Buchwald amination/cyclization; palladium catalysis; pyrido[2,3-b]quinoxaline-3-carboxylates